The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ejca.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

RNASeq analysis reveals biological processes governing the clinical behaviour of endometrioid and serous endometrial cancers

Abstract: Background Endometrial carcinoma comprises a group of tumors with distinct histologic and molecular features, and clinical behavior. Here we sought to define the biological processes that govern the clinical behavior of endometrial cancers. Methods Sixteen prototype genes representative of different biological processes that would likely play a role in endometrial and other hormone-driven cancers were defined. RNA-sequencing gene expression data from 323 endometrial cancers from The Cancer Genome Atlas were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…However, in the recurrent setting, reevaluation of MMR status in the operative biopsy should be considered as this may qualify for treatment with immune checkpoint inhibitor. Studies have previously suggested MSH6 as a potential prognostic marker in endometrial cancer, where high MSH6 in hysterectomy tissue is associated with poor outcome and nonendometrioid subtype [19,35]. Our data validate these findings and demonstrates a strong prognostic value in preoperative samples in this large prospective endometrial cancer cohort.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, in the recurrent setting, reevaluation of MMR status in the operative biopsy should be considered as this may qualify for treatment with immune checkpoint inhibitor. Studies have previously suggested MSH6 as a potential prognostic marker in endometrial cancer, where high MSH6 in hysterectomy tissue is associated with poor outcome and nonendometrioid subtype [19,35]. Our data validate these findings and demonstrates a strong prognostic value in preoperative samples in this large prospective endometrial cancer cohort.…”
Section: Discussionsupporting
confidence: 87%
“…High MSH6 also yields prognostic value across other cancer types, suggesting that MSH6 may function to promote aggressive tumour behaviour [13][14][15][16][17]19]. However, the mechanism underlying overexpression of MSH6 is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Goodfellow et al, in a cohort of 1002 patients with EC, showed that the most common MMR defect was MLH1 loss followed by combined MSH2/MSH6 losses, then MSH6 loss alone at 70%, 20.5%, and 19.6%, respectively [ 71 ]. Several articles highlighted an increased prevalence of MSH6 mutations representing 3.8% (95% CI 1.0–9.5%) of patients with EC compared to 2.6% (95% CI 0.5–7.4%) of patients with HNPCC tumors [ 167 , 168 , 169 ]. It is, thus, essential to screen patients with EC with IHC using the four proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we used bioinformatics and statistical tools to systematically analyze the prognostic accuracy of lncRNAs associated with mesenchymal subtype, similar to the construction of immune-related lncRNAs model (46). We integrated multiple MES-related lncRNAs into a single model and explored whether the model played a more important role in the prognostic evaluation of gliomas.…”
Section: Discussionmentioning
confidence: 99%